Antibacterial Activity Test of Malacca Leaf Extract (Phyllanthus emblica) Against Staphylococcus aureus and Staphylococcus epidermidis Bacteria - Ridwanto, Ridwanto; Aprilia, Hijjatun; Rani, Zulmai; Putri Aisyia Fauzi, Ziza; Kaban, Vera Estefania; Nasri, Nasri (Talenta Publisher, 2024)
Antibacterials are substances that can interfere with the growth or even kill bacteria and have the side effect of antibacterial resistance. One effort to reduce resistance is choosing to use natural bacterial ingredients. One plant that can potentially contain antibacterial activity is malacca leaves (Phyllanthus emblica). The contents of this plant include flavonoids, alkaloids, tannins, saponins, and steroids/triterpenoids. This research aimed to prove the antibacterial activity test of malacca leaf extract. The stages in this research included phytochemical screening and testing the antibacterial activity of ethanol extract from Malacca leaves for Staphylococcus aureus and Staphylococcus epidermidis bacteria using the diffusion method using paper discs. The characteristics of malacca leaf simplicia obtained were water content of 4.6%, water-soluble content of 28%, ethanol-soluble essence content of 23.33%, total ash content of 2.00%, and insoluble ash content of 0.5%. The results of phytochemical screening showed the presence of flavonoids, saponins, tannins, glycosides, and steroids/triterpenoids. The antibacterial test results of malacca leaf extract at concentrations of 500 mg/ml, 400 mg/ml, 300 mg/ml, and 200 mg/ml have an antibacterial effect against Staphylococcus aureus and Staphylococcus epidermidis, and there is no difference in the effectiveness of the inhibitor against gram-positive and negative grams.